Dampak Perkembangan Objek Wisata Terhadap Peralihan Pekerjaan dan Peluang Kerja di Kecamatan Tomohon Barat - Endah Mardiana; Xaverius Erick Lobja; Muhammad Isa Ramadhan (GEOGRAPHIA : Jurnal Pendidikan dan Penelitian Geografi, 2024)
The study examines the job transition of supporting business actors at tourist attractions in West Tomohon District and the job opportunities in tourism-supporting businesses. The research involved 31 respondents from Welu and Kaisanti tourist attractions. The findings revealed that the existence of tourist attractions in Woloan Satu Utara and Woloan Dua sub-districts influences job transition, with 68% of respondents switching jobs. Forty-eight percent of casual daily laborers, including motorbike taxis, drivers, and construction workers, chose to become tourism entrepreneurs. Sixty-seven percent of respondents switched jobs to earn more income. The study also found that tourist attractions positively impact the surrounding community by providing employment opportunities and promoting various businesses, contributing to the economic development of the area..